Alat Pengukur Suhu Tubuh Berbasis Wireless Sensor Network - Eri Mardiani; Andri Cahyo Purnomo; Jose Armando; Fuad Alfarizi (UNIVERSITAS RAHARJA, 2024)
Human body temperature can be measured using a thermometer. Thermometers currently available include analog thermometers and digital thermometers. This tool usually takes up to 1-2 minutes to detect body temperature readings. Therefore, a new method is needed to obtain body temperature values in a shorter time without sacrificing accuracy. As part of this research, a tool has been developed that can measure human body temperature values in a short time and provide accurate readings, as well as a monitoring tool. The tools used in this research are the MLX90614 series infrared sensor, ultrasonic distance sensor, NRF24L01 series wireless sensor, and a sound sensor, namely a buzzer, combined with an Arduino Nano and Uno with an I2C LCD screen, made in such a way that the thermometer is without physical contact. The research methods used include observation, interviews and literature reviews, as well as the use of the Throw Away Prototyping design method and R&D methods. Based on the results of tests carried out, this sensor detects the temperature of objects at a distance of 0-5cm and issues a warning if the temperature is > 37'C.